ANALYSIS OF FOLK TALES AND THEORETICAL ASPECTS OF THE GENRE - Abdurashidova, Nilufar (Журнал иностранных языков и лингвистики, 2023)
Ancient traditions, rituals and legends play a key role in the creation of fairy tales in our article. The fairy tale world is a separate genre, since the life of tribes and clans during this period is associated with legends, and traditional traditions with certain events and phenomena lose their power and vital function. It was gradually understood as something strange in people's minds.